The impact of international remittances on food security during the Covid-19 pandemic: evidence from Malawi - Martins, Tiago João Carvalho (2022)
This is the first paper to study the impact of international remittances on household food security after the COVID-19 pandemic outbreak. Using nationally representative quarterly panel data from the Malawi High-Frequency Phone Survey on COVID-19, it employs an instrumental variable approach to address the endogeneity of the international migrant remittances. The results show a positive and significant impact of remittances on food security, especially in households headed by a female member during the pandemic outbreak year. These results are robust to the use of different food security measures and to controlling for the influence of social safety nets.